WIDGET: The WatriImed knowleDGe Exploration Tool - (:unkn) unknown (My University, 2020)
In this paper, we describe the WATRIMed (West African Herbal Traditional Medicine) Knowledge Graph visualisation tool, WIDGET. It enables a set of e-health services and will contribute in increasing patient safety in the context of herbal-based African Traditional Medicine. Users can browse in medicinal recipes for a given symptom or disease. The recipes consist in medicinal plants with proven effectiveness. It is therefore possible to access the information of the recipe composition and that of the plants. It also allow cross-linking most of common dialects of West Africa, their geographic distribution, and the name of plants in these ethnic dialects. Thus, from the symptoms, available indications in different West African regions are provided.
Keywords: African Research